Atmospheric deposition of inorganic nitrogen in Spanish forests of Quercus ilex measured with ion-exchange resins and conventional collectors. (September 2016) - García-Gomez, Héctor; Izquieta-Rojano, Sheila; Aguillaume, Laura; González-Fernández, Ignacio; Valiño, Fernando; Elustondo, David; Santamaría, Jesús M.; Àvila, Anna; Fenn, Mark E.; Alonso, Rocío
Abstract: Atmospheric nitrogen deposition is one of the main threats for biodiversity and ecosystem functioning. Measurement techniques like ion-exchange resin collectors (IECs), which are less expensive and time-consuming than conventional methods, are gaining relevance in the study of atmospheric deposition and are recommended to expand monitoring networks. In the present work, bulk and throughfall deposition of inorganic nitrogen were monitored in three different holm oak forests in Spain during two years. The results obtained with IECs were contrasted with a conventional technique using bottle collectors and with a literature review of similar studies. The performance of IECs in comparison with the conventional method was good for measuring bulk deposition of nitrate and acceptable for ammonium and total dissolved inorganic nitrogen. Mean annual bulk deposition of inorganic nitrogen ranged 3.09–5.43 kg N ha −1 according to IEC methodology, and 2.42–6.83 kg N ha −1 y −1 using the conventional method. Intra-annual variability of the net throughfall deposition of nitrogen measured with the conventional method revealed the existence of input pulses of nitrogen into the forest soil after dry periods, presumably originated from the washing of dry deposition accumulated in the canopy. Important methodological recommendations on the IEC method and discussed, compiled and summarized. Highlights: Ion-exchange resin collectors are recommended for Mediterranean long-term studies. Resin method worked well for bulk deposition of nitrate and acceptably for ammonium. Methodological recommendations for surveys in Mediterranean Region are presented. Episodic inputs of nitrogen into the forest soil after dry periods are described. Abstract : Ion-exchange resin collectors are recommended for long-term studies of nitrogen deposition in Mediterranean Europe and methodological recommendations are presented.